(untitled) - James, William (New York, NY, 1988)
Contents is the varieties of religious experience; pragmatism; a pluralistic universe; the meaning of truth; some problems of philiosophy.
Keywords: Psychology,Pragmatism,Philosophy,Experience ( Religion ); Religious